Comparison of 8 Weeks of Selected TRX Training and Weight Training on Improving Motor Function and Chronic Nonspecific Back Pain in Women Aged 35 to 55 - Fatemeh Rezaei (Biyumikānīk-i varzishī)
Objective The aim of this study was to compare the effects of 8 weeks of selected TRX exercises and weight training on improving motor function and chronic nonspecific low back pain in women aged 35 to 55 years. Methods Thirty female patients with chronic nonspecific back pain, who were willing to participate in the study, were selected and divided into two groups: weight training (Age: 44.20 ± 7.46 years, Height: 1.65 ± 0.03 m, Weight: 58.60 ± 3.69 kg, Body Mass Index: 21.38 ± 1.76 kg/m²) and TRX (Age: 47.26 ± 5.86 years, Height: 1.66 ± 0.02 m, Weight: 56.13 ± 4.40 kg, Body Mass Index: 20.18 ± 1.32 kg/m²). After group assignment, kyphosis and lordosis were measured using a flexible ruler, and functional movement was assessed with the Functional Movement Screening (FMS) test. Pain levels were recorded using a pain questionnaire. Both groups performed their respective exercises for 8 weeks, with 3 sessions per week. Post-test measurements were conducted after the 8-week intervention. To analyze the data and determine any significant differences between group means at various stages, statistical methods such as analysis of covariance, paired t-tests, Mann-Whitney U tests, and Wilcoxon tests were used, depending on the normality of data distribution. Results The results of this study demonstrated that both weight training (P ≤ 0.01) and TRX (P ≤ 0.01) programs significantly reduced pain, improved motor function, and decreased kyphosis and lordosis. When comparing the two training groups, no significant differences were observed except in the kyphosis variable (P = 0.002), where a difference was found (P > 0.05). Conclusion Both types of exercises were effective in strengthening the trunk area, reducing pain, and addressing musculoskeletal disorders. These exercises appear to lower the risk of injury and enhance performance by improving motor function. Additionally, by applying theories that emphasize strengthening the core muscles and mobilizing the limbs, it can be concluded that participation in these exercises improves the performance of women suffering from musculoskeletal pain.